2011
DOI: 10.2478/v10181-011-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of selected seminal plasma proteins and their application in the improvement of the reproductive processes in mammals

Abstract: Understanding the biochemical processes associated with ovum fertilization and knowledge about the structure and function of individual substances participating in these processes is crucial for the development of biotechnological methods to improve reproduction of animals and humans. Among many components of seminal plasma, proteins and peptides play a specific role in regulation of the fertilization process, particularly through their ability to bind various types of ligands such as polysaccharides, lipids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Result of a study by Mogielnicka-Brzozowska et al (2011) also indicated that zona binding proteins of boar seminal plasma have a shielding effect on the plasma membrane and the acrosome of spermatozoa by protecting their structures against the damage caused by cold shock. Mogielnicka-Brzozowska and Kordan (2011) mentioned that addition of specific plasma protein to sperm probably may retain the features responsible for the efficient fertilization after storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Result of a study by Mogielnicka-Brzozowska et al (2011) also indicated that zona binding proteins of boar seminal plasma have a shielding effect on the plasma membrane and the acrosome of spermatozoa by protecting their structures against the damage caused by cold shock. Mogielnicka-Brzozowska and Kordan (2011) mentioned that addition of specific plasma protein to sperm probably may retain the features responsible for the efficient fertilization after storage.…”
Section: Resultsmentioning
confidence: 99%
“…Absorption of isolated proteins from the seminal plasma can reduce the damage that cold shock can have on the sperm membrane (Barrios et al, 2000). Mogielnicka-Brzozowska and Kordan (2011) mentioned the possibility of adding specific plasma proteins to sperm for the retention of features responsible for the efficient fertilization after storage. HBPs protect sperm from stress of freezing and thawing and maintained intracellular protein homeostasis (Shi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In other livestock species including the bull, ram and boar, numerous proteins have been identified that play an integral role in sperm function, binding with the sperm membrane and initiating capacitation and the acrosome reaction (Maxwell et al. 2007; Mogielnicka‐Brzozowska and Kordan 2011) as well as enhancing sperm‐oocyte binding. Mass spectrometry analysis of pooled alpaca seminal plasma identified 89 proteins, of which 28 have previously been reported in the seminal plasma of other species and have been associated with sperm function, integrity and fertilizing ability (Table 3, C. M. Kershaw‐Young, X. Druart and W. M. C. Maxwell, unpublished).…”
Section: Proteins In Camelid Seminal Plasmamentioning
confidence: 99%
“…Results of a study by Mogielnicka-Brzozowska et al [17] indicated that zinc-binding proteins of boar seminal plasma have a shielding effect on the plasma membrane and acrosome of spermatozoa, protecting these structures against consequences of cold shock. Mogielnicka-Brzozowska and Kordan [18] mentioned the possibility of adding specific plasma proteins to sperm for the rentention of features responsible for the efficient fertilization after storage.…”
Section: Introductionmentioning
confidence: 99%